(untitled) (JOSAR (Journal of Students Academic Research), 2025)
The purpose of the study was to obtain empirical data on the PBL model with a flipped learning approach that can improve students’ critical thinking skills. The research subjects were Al Muhafizhoh High School students in class XI IPA, two classes, totaling 46 children, Pancasila education mapel. Type of quantitative research, using an experimental approach. Research data initial test scores and final tests and questionnaires. Experimental design one group pre test and post test. From the results of hypothesis testing using the t-test formula the results obtained t (count) ˃ t (table), where t count = 3.14 while t table = 2.02, with a significant level of 0.05, it can be concluded that PBL with a flipped learning approach at Al Muhafizhoh Senior High School in Blitar City has an effect on students’ critical thinking skills.